Antioxidant activity of Jinxuan tea polysaccharide and its protective effect on intestinal injury induced by transport stress in chicks - Sun, Xueyan; Zhou, Qiaoyi; Gao, Jinjing; Liu, Shujuan; Zhao, Feike; Ling, Caijin; Fang, Binghu (Frontiers in Veterinary Science, 2025)
IntroductionTransport stress (TS) is unavoidable for livestock and poultry in modern agriculture, which not only affects animal welfare, but also to the quality of meat products. Tea polysaccharide (TPS), one of the major bioactive components of tea leaves, has been shown to have anti-stress effects. However, the antagonistic effect of TPS on TS-induced intestinal damage in chicks is unclear.MethodsThe free radical scavenging and reducing abilities of TPS were determined by chemical methods. RAW264.7 macrophages were stimulated by H2O2 to construct cell oxidative damage model, and the effects of TPS on cell viability and antioxidant enzyme activity were determined. A chick transport stress model was established using the shaker to investigate the effect of TPS on intestinal damage in chick caused by transport stress.ResultsIn vitro test results showed that TPS had good free radical scavenging ability and reducing ability. Furthermore, TPS could significantly alleviate cell oxidative damage induced by H2O2. In vivo test results showed that the TS-induced intestinal pathological damage and oxidative damage were markedly alleviated by TPS. Furthermore, TS resulted in the elevated expression of heat shock factors, disrupted expression of heat shock proteins, and similarly disrupted expression of aquaporins in chicks. Surprisingly, chicks treated with TPS showed a significant decrease in the expression of heat shock factors and significant alleviation of the dysregulated expression of heat shock proteins and aquaporins. Analysis of the intestinal flora showed that TS resulted in reduced intestinal flora diversity and altered flora structure in chicks, whereas the intestinal flora was normalized after TPS intervention.DiscussionTPS has good antioxidant activity and significantly ameliorate TS-induced intestinal damage in chicks, suggesting that TPS could be developed and utilized as a feed additive.